An innovative approach of alternating magnetic field diversified with different wave types and magnet positions for ferrofluid flow in dimpled tube - Gürdal, Mehmet; Gürsoy, Emrehan; Pazarlıoğlu, Hayati Kadir; Arslan, Kamil; Gedik, Engin (Elsevier BV, 2023)
The purpose of the present experimental study is to investigate the forced magneto-convection of the Fe3O4/H2O ferrofluid flowing along smooth and dimpled tubes implemented with alternating magnetic field (B = 0.16 T and f = 5 Hz). All experiments were carried out for the working fluids pure water and ferrofluid with 1.0% volume fraction in the laminar flow regime (1131 ≤ Re ≤ 2102). Also, an original perspective of this study is to use of changing magnetic field wave types (Sinus, Triangle, and Square) and positions at different axial distances (x/D = 20, x/D = 40, and x/D = 60). Findings shed light on that the highest convective heat transfer ratio was realized at x/D = 20 location and square wave type for all cases. The average Nusselt number of the dimpled tube subjected to square wave type applied at x/D = 20 is increased by 58.13% compared to smooth tube without magnetic field and using H2O as working fluid. Moreover, when the friction factor was compared for the same conditions, the increment rate has been seen by 85.73%. Although Nusselt number is reached to its highest level using square wave type, the highest Performance Evaluation Criteria is detected around 1.45 using dimpled tube subjected to alternating magnetic field with triangle wave type applied at x/D = 20 for Re = 1131.